(untitled) (Economic studies journal, 2025)
This study aims to examine and analyses the causal relationship between inflation rate and growth rate of the monetary base in the Libyan economy during the period (2004–2022), using monthly data. The analysis investigates the extent of causal linkages, whether unidirectional or bidirectional, by applying the Toda–Yamamoto approach to identify long-run causality. The findings of the study reveal the existence of a unidirectional causal relationship running from inflation to the growth of the monetary base in the Libyan economy during the study period.